Peran Hukum dalam Mengatasi Kejahatan Implementasi Digital dan Perlindungan Data Diri - Dzikrillah, Medina Lailatul; Arddiansyah, Firmanda; Pranata, Boy Alen; Zunaidi, Arif (Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Darussalam (UID) | Islamic University of Darussalam, Ciamis, Jawa Barat, INDONESIA, 2025)
The development of digital technology in Indonesia has brought a significant impact on various sectors, but it also raises serious challenges in the form of increasing digital crime, especially violations of personal data which is now a commodity that is vulnerable to misuse. As a response to these conditions, the government passed Law Number 27 of 2022 on Personal Data Protection (PDP Law) as an effort to provide a strong legal basis in protecting individual privacy rights. This journal aims to analyze the role of law in overcoming digital crime in Indonesia and evaluate the effectiveness of the implementation of the PDP Law in the context of personal data protection. This research uses a normative juridical approach to examine relevant regulations, as well as an empirical juridical approach through interviews and case studies to assess the application of the law in the field. The analysis is conducted qualitatively by focusing on three main aspects, namely the legal basis of personal data protection, the implementation of the law in practice, and the challenges and problems faced in its implementation.